Using cognitive radio scheme for big data traffic management in cellular systems. (2017) - Raiyn, Jamal
This paper introduces the use of the cognitive radio in the cellular system. Cognitive radio Approach aims to manage the traffic flow in dynamic systems. The cognitive radio is a self-aware communication system that efficiently uses spectrum in an intelligent way. The cognitive radio scheme offers several features like autonomy, negotiation and sensing. The use of cognitive radio gives greater autonomy to the base stations. This autonomy allows an increase in flexibility to deal with new situations in the traffic load. The negotiation is used to avoid conflict in the resource allocation. The proposed algorithm is very successful for two reasons. The cognitive radio handles the handoff problem that reduces the handoff blocking rate. The reduction of the call blocking rate in cellular networks will increase the accuracy and the reliability of the forecast model. A number of spectrum sensing techniques have been proposed. A spectrum scheme uses received signals to detect channel states. To improve the performance of spectrum sensing scheme new technique will be added to spectrum scheme. The new technique is channel states forecasting based on quality of experience.